Kemampuan Mendengarkan Drama „Die Räuber“ Karya Friedrich Schiller - Muh. Aslan Pratama Putra; Syamsu Rijal; Syarifah Fatimah (Phonologie : Journal of Language and Literature, 2021)
Abstract. This research is descriptive quantitative which aims to determine the ability and factors that influence listening to the drama "die Räuber" by Friedrich Schiller of 11th grade students of Islamic High School 1 Makassar. The population of this research 11th grade students “Math and Sciense Major (MIA) 5 of Islamic High School 1 Makassar with the total of 40 students. The sample of this research is 40 students obtained using Total Sampling. The data of this research was obtained through a listening test for the drama "die Räuber" by Friedrich Schiller and the provision of a questionnaire. The results of the listening test showed an average score of 75.6% and were in the good category. From the results of the distribution of the questionnaire data obtained that there are two factors that play an important role in influencing students' listening skills, namely: 1) Supporting factors, students are interested and enthusiastic in participating in learning to listen to German drama. 2) The inhibiting factor, students get bored easily and lack the potential to listen to German dramas.